Saliva immunoglobulins in elite women rowers - Nehlsen-Cannarella, S. L.; Nieman, D. C.; Fagoaga, O. R.; Kelln, W. J.; Henson, D. A.; Shannon, M.; Davis, J. M. (European Journal of Applied Physiology, 2000)
Saliva immunoglobulins (sIgA, sIgG, and sIgM) and upper respiratory tract infection (URTI) rates were evaluated in 20 elite female rowers and 19 nonathletes. Also, the influence of carbohydrate versus placebo beverage consumption on saliva immunoglobulin responses to rowing training sessions was measured in 15 rowers and in 5 non-exercising rowers. Saliva samples were collected 1 day before, and 5-10 min and 1.5 h after rowing or rest. Pre-exercise sIgA (but not sIgG or sIgM) concentration was 77% higher in the rowers compared to nonathletes (P < 0.001). Health records kept over 2 months revealed mean 5.2 (SEM 1.2) and 3.3 (SEM 1.1) days with URTI symptoms for the rowers and controls, respectively. For all 39 subjects, and for the 20 rowers separately, no significant correlation was found between URTI symptoms or insulin, cortisol, and growth hormone concentrations and pre-exercise or exercise-related changes in saliva immunoglobulin concentrations or secretion rates. The patterns of change in saliva immunoglobulin concentration and secretion rate did not differ between the carbohydrate and placebo rowing trials, or between exercised and rested athletes. These data indicated an increased sIgA concentration in the female elite rowers compared to the nonathletes, no association between saliva immunoglobulins and URTI, and no effect of a normal 2-hour training session or carbohydrate ingestion on saliva immunoglobulin concentrations or secretion rates.